Pharmaceutical formulation based on chitosan and Schinus terebinthifolius Raddi extract: development and technological study (Research, Society and Development, 2022)
Aroeira-vermelha, as Schinus terebinthifolius Raddi is known, is a plant species from the Anacardiaceae family, present in almost all Brazilian territory. There is scientific evidence that the species has bioactive compounds, for example, flavonoid, tannins, terpenes and phenols groups in their composition, which suggests a broad spectrum of pharmacological activities for the plant, such as anti-inflammatory, antioxidant, anticancer and healing. Thus, aroeira presents great potential for the production of phytotherapics. Therefore, this work aimed at the development and production of gel formulations containing the extract of S. terebinthifolius together with chitosan and Carbopol, as well as characterizing them. The stability tests were applied to both formulations, the results demonstrate that they did not suffer any interference in their organoleptic characteristics, however regarding the pH and electrical conductivity there were some changes in the gel with chitosan. This studyelaborated formulations, after technological tests, demonstrated stability in all stages of development, for both excipients. Given these results, this phytopharmaceutical proved to be an excellent therapeutic alternative for topical use.